Increased myocardial native T1 and extracellular volume in patients with Duchenne muscular dystrophy. Issue 1 (December 2015) - Soslow, Jonathan; Damon, Stephen; Crum, Kimberly; Lawson, Mark; Slaughter, James; Xu, Meng; Arai, Andrew; Sawyer, Douglas; Parra, David; Damon, Bruce; Markham, Larry
Abstract Background Duchenne muscular dystrophy (DMD) cardiomyopathy is a progressive disease for which there is no cure. Disease-specific therapies are needed that can be initiated before irreversible myocardial damage ensues. In order to evaluate therapeutic efficacy, surrogate endpoints other than ejection fraction must be found. The hypothesis of this study is that T1 and extracellular volume fraction (ECV) mapping using cardiovascular magnetic resonance (CMR) can detect diffuse extracellular matrix expansion in DMD patients with normal left ventricular ejection fraction (LVEF) and without myocardial late gadolinium enhancement (LGE). Methods Thirty-one DMD and 11 healthy control participants were prospectively enrolled. CMR using a modified Look-Locker (MOLLI) sequence was performed in all participants before and after contrast administration. T1 and ECV maps of the mid left ventricular myocardium were generated and regions of interest were contoured using the standard 6-segment AHA model. Global and segmental values were compared between DMD and controls using a Wilcoxon rank-sum test. Results The DMD participants had significantly higher mean native T1 compared with controls (1045 ms vs 988 ms, p = 0.001). DMD participants with normal LVEF and without evidence of LGE also demonstrated elevated mean native T1 (1039 ms vs 988 ms, p = 0.002, and 1038 ms vs 988 ms, p = 0.011). DMD participants had a significantly greater mean ECV than controls (0.31 vs 0.24, p < 0.001), even in the settings of normal LVEF (0.28 vs 0.24, p < 0.001) and negative LGE (0.29 vs 0.24, p = 0.001). Conclusions DMD participants have elevated LV myocardial native T1 and ECV, even in the setting of normal LVEF and in the absence of LGE. T1 and ECV mapping in DMD have potential to serve as surrogate cardiomyopathy outcome measures for clinical trials.